Lightweight high-strength bulk amorphous carbon block and preparation method thereof
By using bidirectional pressure and discharge plasma sintering technology assisted by carbon black powder and graphite mold, the problem of difficulty in preparing large-sized, lightweight, and high-strength amorphous carbon blocks in the prior art is solved, and efficient and economical amorphous carbon block preparation is achieved, with excellent room temperature conductivity and industrial production potential.
Patent Information
- Application Number
- CN202510137910.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-15
AI Technical Summary
It is difficult to prepare large-size, lightweight, high-strength glass carbon or amorphous carbon blocks in the prior art, and the samples synthesized at high temperature and high pressure are small in size, complex in process and low economic benefits.
Carbon black powder is used as the precursor, and large amorphous carbon blocks with a density of 1.1-1.4 g/cm3 are prepared by assisting graphite molds and graphite paper, using bidirectional pressure and discharge plasma sintering technology.
Large-sized, lightweight, and high-strength large amorphous carbon blocks have excellent room temperature conductivity, can be used instead of graphite materials, and have the economic benefits of large-scale production.
Smart Images

Figure CN119822833A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of amorphous carbon block materials, and in particular to a lightweight and high-strength large-block amorphous carbon block material and a preparation method thereof. Background Art
[0002] Amorphous materials refer to materials that lack long-range ordered atomic arrangement. Unlike crystalline materials, their atomic or molecular arrangement is random or short-range ordered. The unique microstructure makes amorphous materials have some excellent properties that the corresponding crystalline materials do not have. Among them, amorphous carbon block is an important type of amorphous material, mainly composed of sp, sp 2 and sp 3 It is composed of hybrid carbon atoms and has the characteristics of "long-range disorder and short-range order". Its "short-range order" structure has many possible forms, such as graphene-like structure and diamond-like structure, so it exhibits excellent physical and chemical properties, such as high mechanical properties, thermal stability, electrical conductivity, and environmental friendliness. Therefore, amorphous carbon blocks have broad application prospects in the fields of mechanical manufacturing, electrical and electronics, aerospace, energy storage, etc.
[0003] There are few types of amorphous carbon blocks, and the most common ones are glassy carbon. The density of glassy carbon is 1.4-1.5g / cm 3 , which is only about 60% of the density of graphite, but its mechanical properties such as hardness, wear resistance, compression strength, and flexural strength are much higher than those of graphite blocks. At present, the commonly used methods for preparing glassy carbon include casting molding, centrifugal molding, multi-layer coating molding, mold / extrusion molding, etc. The basic process is to use high-temperature pyrolysis of high-molecular polymers such as furfuryl alcohol resin and phenolic resin. However, since a large amount of water and other small molecular substances will overflow in the process of converting polymers into glassy carbon, cracks and open pores are prone to occur in the process of preparing larger-sized blocks, resulting in cracking of the finished product. Therefore, it is difficult to obtain glassy carbon products with a thickness greater than 5 cm. In recent years, people have also tried to use fullerenes, nanodiamonds, etc. as raw materials, and obtained several amorphous carbon blocks by high temperature and high pressure methods. Due to the limitations of synthesis equipment, samples synthesized by high temperature and high pressure are often small in size, and face problems such as harsh conditions, complex processes, low yields, and high equipment requirements. In addition, raw materials such as fullerenes and nanodiamonds are expensive and have low economic benefits, which further limits large-scale production. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a lightweight and high-strength bulk amorphous carbon block and a preparation method thereof. The prepared bulk amorphous carbon block has the properties of large size, light weight, high strength, high hardness, etc., and at the same time has high room temperature conductivity, and can be used in specific fields instead of graphite materials.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A lightweight, high-strength bulk amorphous carbon material, the amorphous carbon material is composed of disordered multi-layer graphene-like fragments and has a density of 1.1-1.4 g / cm 3 .
[0007] The present invention also provides a method for preparing a lightweight and high-strength large-block amorphous carbon material, comprising the following steps:
[0008] Step 1, ingredients: weigh an appropriate amount of carbon black powder as raw material;
[0009] Step 2, loading: Use graphite paper to wrap the carbon black powder weighed in step 1 and place it in a graphite mold, and vibrate it several times to eliminate internal pores;
[0010] Step 3, pre-pressing: applying bidirectional pressure to the powder loaded in the graphite mold in step 2, and maintaining the pressure for a period of time, and obtaining a pre-pressed blank after pre-pressing;
[0011] Step 4, sintering: the graphite mold in step 3 is wrapped with carbon felt and placed together with the pre-pressed green sheet in a sintering device, and sintering pressure is applied in a specific sintering atmosphere. After the sintering pressure is stable, the temperature is raised to the target temperature in a stepwise manner and kept warm. After the holding time is over, the pressure is released, and the temperature is slowly lowered in stages to room temperature;
[0012] Step 5: Discharging: Take out the graphite mold and demould to obtain a lightweight and high-strength large-scale amorphous carbon block.
[0013] Furthermore, in step 1, the carbon black powder used is obtained by continuous pyrolysis of acetylene, has a purity of more than 99%, is 100% compressed, and has a particle size distribution of 20-100 nm.
[0014] By adopting the above technical solution: the precursor carbon black used is a natural carbon material, which is environmentally friendly, has a wide source of raw materials and is inexpensive. As a precursor, it has significant economic benefits and is characterized by large-scale production.
[0015] Furthermore, in step 2, the carbon black powder weighed in step 1 is wrapped with graphite paper and placed in a graphite mold.
[0016] By adopting the above technical solution: using a sintering mold instead of a molding mold for pre-pressing, the carbon black powder is directly placed in a graphite mold for pre-pressing, thereby avoiding damage and cracking of the pre-pressed green sheet when it is taken out of the molding mold. In addition, graphite paper is used to assist sintering and demolding, and a layer of graphite paper is placed between the graphite mold and the pre-pressed green sheet to prevent adhesion between the pre-pressed green sheet and the graphite mold during the sintering process, thereby avoiding forcibly removing the block during demolding, resulting in sample cracking or mold damage. At the same time, graphite paper can better maintain the sintering atmosphere, thereby improving sample performance.
[0017] Furthermore, in step 3, the bidirectional pressure used is 5-15 MPa, and 10 MPa is most preferred. The holding time is 5-15 min, and 10 min is most preferred.
[0018] By adopting the above technical solution: bidirectional pressurization is used instead of unidirectional pressurization during pre-pressing of the pre-pressed green body. Bidirectional pressurization can effectively avoid the pressure gradient inside the green body, which leads to uneven contact of powders, resulting in density difference in the pre-pressed green body, thereby affecting the formability and stability of the subsequent sintered samples.
[0019] Furthermore, in step 4, the sintering equipment is a spark plasma sintering equipment.
[0020] By adopting the above technical solution: using spark plasma sintering, the heating speed is fast and the sintering time is short, which is conducive to the rapid sintering and molding of the sample, thereby avoiding excessive graphitization transformation of carbon black during long-term sintering.
[0021] Furthermore, in step 4, the sintering atmosphere is a vacuum atmosphere (<10Pa) or an argon atmosphere, the sintering pressure is 40-55MPa, the sintering temperature is 1700°C-2200°C, and the holding time is 2-10min.
[0022] Furthermore, in step 4, the temperature is increased in a stepwise manner: the first stage is increased from the initial temperature to 100°C before the target temperature, and the heating rate is 80-100°C / min; the second stage is increased to the target temperature, and the heating rate is 50°C / min;
[0023] Slow cooling in stages: the first stage is from the target temperature to 1500℃, the cooling rate is 50℃ / min, and the second stage is furnace cooling, from 1500℃ to room temperature.
[0024] By adopting the above technical solution: wrapping a layer of carbon felt outside the graphite mold, the temperature inside the mold is more uniform, reducing heat loss and improving economic benefits. The sintering atmosphere is vacuum or argon to prevent carbon black powder from oxidizing. The step-by-step heating method can avoid the adverse effects of excessive volume shrinkage caused by rapid phase change of carbon black powder during sintering, and it is also conducive to precise temperature control of sintering equipment.
[0025] The sintering temperature is controlled at 1700-2200°C. This temperature range can effectively sinter the carbon black powder to form an amorphous structure without causing excessive graphitization to cause stratification of the sample.
[0026] The sintering pressure is controlled to be 40-55MPa. This pressure range enables the carbon black powder to be closely contacted and diffused, effectively controlling the transition to graphitization, and obtaining a low-density amorphous carbon block with good formability. At the same time, the applied pressure is small, which is a conventional industrial pressure and can meet the needs of industrial mass production.
[0027] After the insulation is completed, the pressure is released first, and then the temperature is lowered in stages to allow the sample to fully release stress in the high temperature area. The internal temperature of the sample gradually approaches equilibrium to avoid the generation of cracks, improve the formability and mechanical properties of the sample, and improve the sintering efficiency.
[0028] Among them, the sintering device is a domestic spark plasma sintering furnace, such as the FHP-828 sintering furnace of Suzhou Hateng Company, which has low equipment requirements.
[0029] Furthermore, in step 5, the diameter of the large amorphous carbon block is ≥15 mm, the height is ≥5 mm, and the block volume is ≥1000 mm 3 .
[0030] Furthermore, in step 5, the nanoindentation hardness of the bulk amorphous carbon block is 250-650 MPa, the compressive strength is 80-170 MPa, the flexural strength is 25-70 MPa, and the room temperature conductivity is 5800-9500 S / m.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The precursor used in the present invention is widely available and inexpensive, the sintering conditions are mild, the equipment and process are simple, the sintered samples have excellent performance, a wide range of applications, significant economic benefits, and can be mass-produced.
[0033] 2. The large amorphous carbon block prepared by the present invention has the properties of large size, light weight, high strength, high hardness, etc., and also has high room temperature conductivity, and can be used instead of graphite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a physical picture of the large amorphous carbon block prepared in Examples 1-5 of the present invention. (Numbers are 1-5 from left to right, where the diameter and thickness of sample 1 are 20.5 mm and 13.5 mm respectively.)
[0035] Figure 2 This is a sintering process curve diagram of Example 1 of the present invention. (Red is the temperature curve, and black is the pressure curve)
[0036] Figure 3 ae are X-ray diffraction patterns of the bulk amorphous carbon block prepared in Examples 1-5 of the present invention.
[0037] Figure 4 ae are Raman spectra of the bulk amorphous carbon block prepared in Examples 1-5 of the present invention.
[0038] Figure 5 This is a field emission scanning electron microscope (FESEM) image of the bulk amorphous carbon block prepared in Example 1 of the present invention.
[0039] Figure 6 These are the high-resolution transmission electron microscopy (HRTEM) images and selected area electron diffraction images of the bulk amorphous carbon block prepared in Example 1 of the present invention.
[0040] Figure 7 Compressive stress-strain curves of the bulk amorphous carbon blocks prepared in Examples 1-5 of the present invention.
[0041] Figure 8 Nanoindentation loading-displacement curves of the bulk amorphous carbon block prepared in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0043] For the sake of simplicity, some materials, equipment and method steps commonly used in the art are not specified in the examples. All process methods and analytical procedures (and related parameters) not specified in the examples are carried out according to those commonly used by those skilled in the art (for example, according to the recommendations of the instrument manufacturers); materials and equipment without source are conventional laboratory materials and equipment.
[0044] Material
[0045] The carbon black powder used in the present invention is a known material purchased from AlfaAesar Co., Ltd., with a purity of more than 99%.
[0046] Equipment / Test Method
[0047] Spark plasma sintering SPS synthesis equipment (FPH828, Suzhou Hateng Technology Co., Ltd.).
[0048] X-ray diffractometer XRD (Smartlab Rigaku, Japan).
[0049] Raman spectrometer (Horiba Lab RAM HR, Hobriba Group, Japan).
[0050] Transmission electron microscope TEM (Talos F200X, Thermo Fisher Scientific, USA).
[0051] Field emission scanning electron microscope FESEM (Regulus-8100, Hitachi, Japan).
[0052] The sample density was measured using a density tester (AR-300G, Shenzhen Dahong Meituo Density Measurement Instrument Co., Ltd.). The prepared samples were cleaned and dried at 80°C before testing. The test was performed no less than three times, and the arithmetic average was taken as the test result.
[0053] The density of the sample is further calculated by dividing the mass by the volume. Refer to the standard HB5367.7-1986 of the Ministry of Aviation Industry. First, the sample is processed into a cylinder with a diameter of 3mm and a height of 4mm, and the volume V of the sample is obtained according to the cylinder volume calculation formula. Then the sample is dried at 80°C to constant weight (the mass difference between two weighings does not exceed 0.01g), and a high-precision electronic balance is used to test the sample mass m, thereby obtaining the sample density ρ=m / V. There are no less than two samples to be tested, and each sample is tested no less than three times, and the arithmetic mean is taken as the test result. The density values obtained by the two density test methods are consistent.
[0054] The compressive strength and flexural strength were measured according to the method described in GB / T8489-2006. The compressive strength and flexural strength tests were performed using a material mechanical properties testing machine (MTII / Fullman SEMtester2000, USA). The compressive strength test was performed on the test sample at room temperature. The test sample was a cylinder with a diameter of 3 mm and a height of 4 mm. The strain loading rate was 1×10 -4 s -1 The flexural strength test of the test sample was carried out at room temperature. The test sample was a cuboid with a length, width and height of 10 mm × 2 mm × 1.5 mm, and the loading rate was 0.01 mm / min.
[0055] The load-displacement curve of the sample was obtained by using a nanoindenter (NHT3, Anton Paar, Austria), the Poisson's ratio was set to 0.2, and the indenter used in the test was a Berkovich-type diamond indenter. The test load was 100 mN, and the loading, holding, and unloading times were 15 s, 10 s, and 10 s, respectively.
[0056] The room temperature conductivity chamber is measured at room temperature by a ST2258C digital intelligent four-probe conductivity meter.
[0057] Example 1
[0058] A method for preparing a lightweight and high-strength bulk amorphous carbon block comprises the following steps:
[0059] Step 1, ingredients: weigh 4.5 g of carbon black powder as raw material.
[0060] Step 2, charging: the carbon black powder weighed in step 1 is placed in a graphite mold with an inner diameter of 20 mm, lined with graphite paper, and pre-pressed by applying pressure in both directions. The pressure is 10 MPa, and the holding time is 5 min. After pre-pressing, a pre-pressed blank is obtained.
[0061] Step 3, sintering: Wrap the graphite mold with carbon felt and put it into the sintering chamber of spark plasma sintering (SPS) together with the green body. After evacuating to below 10Pa, start to apply sintering pressure, the sintering pressure is 50MPa, and start heating after the pressure stabilizes. Use infrared temperature measurement system, the heating rate is 100℃ / min, after heating to 1700℃, it is heated to 1800℃ at 50℃ / min, and the heat preservation time is 2min. After the heat preservation is completed, cool down to 800℃ at 50℃ / min and release the pressure, turn off the heating program, and wait for the sample to slowly cool to room temperature in the sintering chamber.
[0062] Step 4, discharging: take out the graphite mold, demould to obtain a lightweight and high-strength large-block amorphous carbon material, and cut, wash and polish the prepared sample.
[0063] Example 2
[0064] This embodiment provides a method for preparing a lightweight, high-strength, large-scale amorphous carbon block material. The specific process parameters of the process steps that are different from those of Example 1 are shown in Example 2 in Table 1. Other parameters are the same as those of Example 1.
[0065] Example 3
[0066] This embodiment provides a method for preparing a lightweight, high-strength, large-scale amorphous carbon block material. The specific process parameters of the process steps that are different from those of Example 1 are shown in Example 3 in Table 1. Other parameters are the same as those of Example 1.
[0067] Example 4
[0068] This embodiment provides a method for preparing a lightweight, high-strength, large-scale amorphous carbon block material. The specific process parameters of the process steps that are different from those of Example 1 are shown in Example 4 in Table 1. Other parameters are the same as those of Example 1.
[0069] Example 5
[0070] This embodiment provides a method for preparing a lightweight, high-strength, large-scale amorphous carbon block material. The specific process parameters of the process steps that are different from those of Example 1 are shown in Example 5 in Table 1. Other parameters are the same as those of Example 1.
[0071] Table 1 Sintering parameter comparison table of Examples 1-5
[0072]
[0073] Table 2 Comparison table of performance parameters of high strength amorphous carbon in Examples 1-5
[0074]
[0075] In contrast, Lin et al. (LINK, FANGH, GAOA, et al. Nanoburl Graphites [J]. Adv Mater, 2021, 33 (17): 2007513) prepared a series of high-performance graphite blocks (HPBG) using a mixed powder of nanodiamond (NDP) and graphite as raw materials. Among them, the nanoindentation hardness of NDP-5HPBG (5 represents the mass percentage of NDP in the mixed powder) is 200MPa, which is significantly lower than the lightweight, high-strength bulk amorphous carbon block synthesized in Examples 1-5 of the present invention. And as the sintering temperature of the embodiment increases, the nanoindentation hardness of the bulk amorphous carbon block exceeds that of NDP-10HPBG. The sample prepared in the preferred embodiment 5 exhibits a compressive strength of 169MPa and a flexural strength of 69MPa, which is comparable to that of Toyo Tanso Co., Ltd. ( https: / / www.toyotanso.com / Products / Special_graphite / data.html) The ISO-68 graphite produced is comparable to and higher than other high-performance graphite blocks produced by the company (such as IG-11, ISEM-8, ISO-66), and has a lower density. The electrical conductivity reaches 9300S / m, which is slightly lower than commercial graphite, but much higher than the conductive materials prepared by SPS processing nano-diamonds and other amorphous carbon synthesized under high temperature and high pressure.
[0076] In addition, the existing technology uses high-energy carbon precursors (such as nanodiamonds, fullerenes, and glassy carbon) to prepare amorphous carbon blocks under high temperature and high pressure. The size is usually limited to less than 5 mm. For example, Shang et al. (SHANGY, LIUZ, DONGJ, et al. Ultrahard bulk amorphous carbon from collapsed fullerene [J]. Nature, 2021, 599 (7886): 599-604) used C 70 As raw materials, the size of amorphous carbon synthesized under high temperature and high pressure is less than 2mm. Another work (SHANGY, YAOM, LIUZ, et al. Enhancement of short / medium-range order and thermal conductivity in ultrahard sp 3 amorphouscarbonbyC 70precursor[J].Nat Commun,2023,14(1):7860) The size of the amorphous carbon block synthesized with fullerene C60 as raw material is less than 1 mm. Moreover, high temperature and high pressure sintering requires a pressure of several or even dozens of GPa, which has high requirements on equipment, harsh preparation conditions and complex process flow. In contrast, the sintering pressure of the present invention is only at the MPa level, the synthesis conditions are mild, and large-sized amorphous carbon blocks can be prepared. For example, the sample prepared in Example 1 has a diameter of 20.5 mm and a thickness of 13.5 mm, which can meet the needs of industrial production.
[0077] In summary, the large amorphous carbon block prepared by the present invention has the properties of large size, light weight, high strength, high hardness, etc., and also has high room temperature conductivity, and can be used instead of graphite materials.
[0078] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.
Claims
1. A lightweight, high-strength bulk amorphous carbon block, characterized in that: The amorphous carbon block is composed of disordered multi-layer graphene-like fragments and has a density of 1.1-1.4 g / cm 3 .
2. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 1, characterized in that: The steps include: Step 1, ingredients: weigh an appropriate amount of carbon black powder as raw material; Step 2, loading: Use graphite paper to wrap the carbon black powder weighed in step 1 and place it in a graphite mold, and vibrate it several times to eliminate internal pores; Step 3, pre-pressing: applying bidirectional pressure to the powder loaded in the graphite mold in step 2, and maintaining the pressure for a period of time, and obtaining a pre-pressed blank after pre-pressing; Step 4, sintering: Wrap the graphite mold in step 3 with carbon felt and put it into the sintering equipment together with the pre-pressed green sheet, start to apply sintering pressure in the sintering atmosphere, and after the sintering pressure is stable, heat it up to the target temperature in a stepwise manner and keep it warm. After the holding time is over, release the pressure and cool it down slowly in stages to room temperature; Step 5: Discharging: Take out the graphite mold and demould to obtain a lightweight and high-strength large-scale amorphous carbon block.
3. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 2, characterized in that: In step 1, the carbon black powder used is obtained by continuous pyrolysis of acetylene, has a purity of more than 99%, is 100% compressed, and has a particle size distribution of 20-100nm.
4. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 2, characterized in that: In step 3, the bidirectional pressure used is 5-15 MPa, and the pressure holding time is 5-15 min.
5. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 2, characterized in that: In step 4, the sintering equipment is a spark plasma sintering equipment.
6. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 2, characterized in that: In step 4, the sintering atmosphere is a vacuum atmosphere or an argon atmosphere, the sintering pressure is 40-55 MPa, the sintering temperature is 1700° C.-2200° C., and the holding time is 2-10 min.
7. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 2, characterized in that: In step 4, the temperature is increased in a stepwise manner: the first stage is increased from the initial temperature to 100°C before the target temperature, and the heating rate is 80-100°C / min; the second stage is increased to the target temperature, and the heating rate is 50°C / min; Slow cooling in stages: the first stage is from the target temperature to 1500℃, the cooling rate is 50℃ / min, and the second stage is furnace cooling, from 1500℃ to room temperature.
8. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 2, characterized in that: In step 5, the diameter of the large amorphous carbon block is ≥15mm, the height is ≥5mm, and the block volume is ≥1000mm 3 .
9. The method for preparing a lightweight, high-strength bulk amorphous carbon block according to claim 2, characterized in that: In step 5, the nanoindentation hardness of the bulk amorphous carbon block is 250-650 MPa, the compressive strength is 80-170 MPa, the flexural strength is 25-70 MPa, and the room temperature conductivity is 5800-9500 S / m.